2021
DOI: 10.3390/separations8060080
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Analytical Method for Deacetylasperulosidic Acid, Asperulosidic Acid, Scopolin, Asperuloside and Scopoletin in Fermented Morinda citrifolia L. (Noni)

Abstract: Fermentation is a technology that enhances biologically active ingredients, improves the absorption rate and induces the generation of new functional ingredients by the catalytic action of enzyme systems possessed by microorganisms. In this study, changes in the content of five kinds of bioactive compounds (deacetylasperulosidic acid, asperulosidic acid, scopolin, asperuloside and scopoletin) of Morinda citrifolia L. were confirmed by fermentation, and a high-performance liquid chromatography-photodiode array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…However, Cheng et al [11] and Wang et al [12] reported that they could improve the smell of M. citrifolia fruit through fermentation. Furthermore, in our previous study, we confirmed that the content of deacetylasperulosidic acid (DAA), a marker compound of M. citrifolia, increased during fermentation [13]. The main phytochemical component of M. citrifolia is iridoid, of which DAA accounts for most [14].…”
Section: Introductionsupporting
confidence: 71%
“…However, Cheng et al [11] and Wang et al [12] reported that they could improve the smell of M. citrifolia fruit through fermentation. Furthermore, in our previous study, we confirmed that the content of deacetylasperulosidic acid (DAA), a marker compound of M. citrifolia, increased during fermentation [13]. The main phytochemical component of M. citrifolia is iridoid, of which DAA accounts for most [14].…”
Section: Introductionsupporting
confidence: 71%
“…Our method showed lower LOD and LOQ for gallic acid [ 14 , 15 ], catechin [ 16 ], scopoletin [ 7 , 18 ] compared to other detection methods. However, better sensitivities were reported for catechin [ 17 ] and scopoletin [ 19 ] due to the highly sensitive detectors (i.e., UHPLC–MS/MS and fluorescence detectors, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The separation and determination of these biomolecules from other plants have been extensively studied in the literature. Numerous analytical methods have been used for gallic acid [ 14 , 15 ], catechin [ 16 , 17 ], and scopoletin [ 18 , 19 ]. However, to the best of the authors’ knowledge, only one analytical method has been reported for the determination of umckalin, through an HPLC-RP method using a C18 column, an isocratic solvent system of acetonitrile-water (45:55, v / v ) flowing at a rate of 0.75 mL/min, and by UV detection at 330 nm [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asperulosidic acid (ASP) is found in Hedyotis diffusa Willd (Rubiaceae) which is widely distributed in China, Indonesia, and other regions in Asia [17][18][19]. ASP is well known for its anti-inflammatory properties [18].…”
Section: Wu/gai/zhangmentioning
confidence: 99%